Analysis of shots and passing sequence of a soccer team and its opponents during 2014 Brazilian championship - Barreira, J.; Vendite, C.; Vendite, L. L. (International Journal of Sports Science, 2016)
The aim of this study was to analyze the shots and passing sequence of a team, and its opponents, during the second division of the 2014 Brazilian Championship. Thirty-eight matches were analyzed and the technical scout was used to quantify the amount of shots and incorrect passes, length of passing sequence and ball possession of both teams per game. The results showed that ball possession and incorrect passes had no relationship with the match outcome. Sequences of three passes or less were the most frequent and most of the shots and goals came from sequences of four and five passes. The main reasons that interrupted passing sequence were: incorrect passes (25%) and loss of ball control (25%), followed by incomplete passes (18%) and fouls (11%). The occurrence of incorrect passes showed a small variability during the championship, from 5% to 12% per game, and presented a significant decrease from the middle to the end of the tournament. The results presented in this study provide valuable information for national coaches for training programs based on real game situations.